Correction to: The burden of war-injury in the Palestinian health care sector in Gaza Strip - Marwan Mosleh; Koustuv Dalal; Yousef Aljeesh; Leif Svanström (BMC, 2018)
In the original publication of this article [1] the background section contained an inaccurate mention of the amount of civilian deaths in the 2014 Gaza war. In this correction article the incorrect and correct information are published for clarification.